Offence of Adultery under IPC: A Critical Evaluation: Examining the Implications of Adultery on Matrimonial Relationships (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Adultery is an offence involving encroachment over right of a husband against his wife. In simple words, it’s an offence against the sanctity of the matrimonial relationship ties, which is always committed by a man . It is an anti-social illegal act.